PENGARUH KEPEMIMPINAN KEPALA DESA TERHADAP TINGKAT PARTISIPASI MASYARAKAT DENGAN PEMAHAMAN MASYARAKAT SEBAGAI PEMODERASI PADA KECAMATAN REJOSO KABUPATEN NGANJUK (Studi Empiris pada Kecamatan Rejoso Kabupaten Nganjuk) - Fetrin Puri Kartikasari; Nur Diana; Siti Aminah Anwar (e_Jurnal Ilmiah Riset Akuntansi, 2021)
The low level of community participation in the use of village funds shows that the implementation of The village still does not fully involve the community in the village financial management process. This matter by the weak influence of leadership caused by the village head as the highest leader who has has full authority and responsibility in managing its territory and community. Low participation the community has an impact on the lack of satisfaction and public trust in the village government. This study uses a correlational quantitative data approach that is supported by primary data. Respondents consisted of 99 people based on profession as civil servants and farmers. The results showed that there were significant influence between the leadership of the village head on community participation in utilization of village funds. there is significant influence between village head leadership and understanding of village funds on community participation in utilization of village funds, and the absence of influence between the interaction of village head leadership and understanding of village funds on the level of community participationKeywords: leadership, participation, understanding, utilization of village funds